DESIGN OF AN ADAPTIVE INTELLIGENT CONTROLLER IN A SEMI-ACTIVE SUSPENSION SYSTEMS - Turnip, Arjon; Soetraprawata, Demi; Hariyadi, -; Kusumandari, Dwi Esti (Teknologi Indonesia, 2013)
In this paper, a semi-active control law consists of two tuneable parameters that are given as the function of the running conditions of the vehicle and an adaptive intelligent controller (AIC) is proposed to obtain the best compromise among confl icting performance indices pertaining to the vehicle suspension system. The proposed AIC method is developed based on the frequency regions. The obtained result indicates that a semi-active suspension system based AIC has a signifi cant potential in improving the ride comfort and the road holding.